Do traumatic events have more impact on the development of dental anxiety than negative, non‐traumatic events?. (29th April 2017) - De Jongh, Ad; van Eeden, Astrid; van Houtem, Caroline M. H. H.; van Wijk, Arjen J.
Abstract : The importance of exposure to traumatic events for the development of dental anxiety has not been investigated. The aim of the present study was to test the hypotheses that individuals who reported having been exposed to a traumatic event [that is, fulfilling Criterion A of the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM‐5), for post‐traumatic stress disorder (PTSD)] as the cause of their dental anxiety would report significantly higher levels of dental anxiety, typical trauma‐related (PTSD) symptoms, and greater disturbance of memories involving these events than those who reported being exposed to non‐traumatic events. Patients of a specialized dental fear clinic ( n = 90) were divided into those who reported a traumatic event that initiated their dental trait anxiety and those who did not. The two groups did not differ in their severity of dental anxiety and number of PTSD symptoms, but the memories of those who had been exposed to traumatic events were significantly more vivid than the memories of those in the reference group. Length of time since the event took place did not play a role. Hence, traumatic events are remembered more vividly, but do not seem to initiate more severe forms of dental anxiety than other events.